SPORT GÚRESINDE OQITIW USILINIŃ TIYKARLARI - Jumaniyazov, Q.T.; Mırzamuratov, J.J. (SCIENCE and SOCIETY, 2022)
This article shows the principles of modern pedagogical training of wrestlers, as an the activity of the teacher.